2020
DOI: 10.1590/2175-6236105412
|View full text |Cite
|
Sign up to set email alerts
|

O Retrato da Exclusão nas Universidades Brasileiras: os limites da inclusão

Abstract: Resumo: O artigo objetiva apresentar um panorama do acesso de pessoas com deficiência ao ensino superior no Brasil. Durante décadas, as políticas públicas têm promovido e defendido práticas educacionais inclusivas, mas, apesar de algumas melhorias, o sistema educacional ainda parece ter dificuldades para acomodar alunos com deficiência. Os dados foram extraídos das bases de dados do Instituto Brasileiro de Geografia e Estatística (IBGE) e do Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
0
0
1
Order By: Relevance
“…In fact, the findings that were found in medical courses reinforces the scenario of exclusion experienced by PWD and has implications for the gains that PWD could attain with the affirmative policies that have been implemented in Brazil. A global analysis of data from 2018 showed that the number of students with disabilities enrolled in private HEI was almost two-fold those who studied in public HEI in Brazil 11 . This picture constitutes an environment of inequality that penalizes students with disabilities, who in addition to having to overcome, throughout their lifetime, several factors that limit access to higher education, add financial commitments that need to be paid for in order to acquire professional training.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the findings that were found in medical courses reinforces the scenario of exclusion experienced by PWD and has implications for the gains that PWD could attain with the affirmative policies that have been implemented in Brazil. A global analysis of data from 2018 showed that the number of students with disabilities enrolled in private HEI was almost two-fold those who studied in public HEI in Brazil 11 . This picture constitutes an environment of inequality that penalizes students with disabilities, who in addition to having to overcome, throughout their lifetime, several factors that limit access to higher education, add financial commitments that need to be paid for in order to acquire professional training.…”
Section: Discussionmentioning
confidence: 99%
“…Frente a la concepción de una política educativa basada en valores y prácticas neoliberales, un significativo número de investigaciones apunta a la necesidad de construir políticas públicas orientadas a la inclusión. La crítica a la base de este desafío es que las políticas de inclusión no favorecen procesos inclusivos (Cabral et al, 2020). Por el contrario, muchas veces predominan racionalidades pragmáticas y neoliberales sin un mayor compromiso por una inclusión genuina.…”
Section: ¿Qué Desafíos Existen Para Avanzar En Inclusión Según Las Pu...unclassified